Potential Role of Tc-99m DTPA Diuretic Renal Scan in the Diagnosis of Calyceal Diverticulum in Children. Issue 24 (June 2015) - Lin, Chun-Chen; Shih, Bing-Fu; Shih, Shin-Lin; Tsai, Jeng-Daw; Bhatt., Girish Chandra
<x xml:space="preserve">Abstract</x> Abstract The aim of the study was to assess the usefulness of Technetium-99m diethylene triamine pentaacetic acid (Tc-99m DTPA) diuretic scan to diagnose calyceal diverticulum (CD). From January 2000 to June 2014, children with evidence of renal cystic lesions of undetermined diagnosis on ultrasound were enrolled. Computed tomography urography (CTU) and Tc-99m DTPA diuretic scan were performed to characterize the precise anatomy. The diagnosis of CD depended on visualization of a renal cystic lesion with filling of contrast material or radiotracer from the collecting system on CTU or diuretic renal scan. Children who had positive findings of CD on 1 or both imaging studies were selected and analyzed. Both CTU and Tc-99m DTPA diuretic renal scan were performed in 39 children. A total of 9 (23.1 %) children with CD were diagnosed. All 9 children had positive diagnosis of CD on diuretic renal scan. Only 6 (66.7%) children could be diagnosed by CTU, and CD was missed by CTU in 3 subjects. The differential renal functions in patients with CD were 46% to 55%. The time of radiotracer appearance in the CD ranged from the 8th to the 24th minute. Seven patients had persistent accumulation of radiotracer in their CD at the end of the study. Tc-99m DTPA diuretic renal scan seems to be more sensitive than CTU in diagnosing CD. The possible reasons of higher sensitivity are discussed. Additional advantages that Tc-99m DTPA diuretic renal scan provides include the following: continuous monitoring, less radiation doses, and information on renal function, making it an attractive alternative to CTU for diagnosis of CD.